Rekonstruksi Pembelajaran Kitab Kuning Untuk Mewujudkan Kemahiran Santri Dalam Memahami Kitab Kuning Di Lembaga Lajnah Bahtsul Masa-Il (LBM) Al-Mahrusiyah Putri - Nisrina Nur Chiari; Reza Ahmad Zahid (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2019)
Reconstruction of â€˜Kitab Kuning learning conducted Lembaga Batsu Masaâ€™il (LBM) Al Mahrusiyah already implemented 2018-2019 school year. Even though it's only been a year, this strategy shows that it can improve the ability of female students to understand the Kitab Kuning. This is proven by the ability of female students who attend LBM to be able to translate and explain the intent contained in the Kitab Kuning. This research uses descriptive qualitative research. The use of research methods is very relevant to the object being studied because researchers become key instruments. The results of this study will describe in full the situation and process of implementing activities in LBM Al Mahrusiyah. Key informants in this study are all stakeholders who are managers, coaches, executors and participants of these activities. The method used is in-depth interviews to find saturated data. An illustration of the results of this study found the application of LBM Al Mahrusiyah held a sifir class, â€œtahasus, ula, wustho, dan ulya.â€ Sorogan class in the realm of reading, â€œmemurodiâ€ (translating) and understanding the Kitab Kuning. In the class of sifir and tahasus the introduction of the kitab kuning and nahwu sharaf science. The book studied varies according to the level of study at each stage of the class.